Knowledge, attitude and practice regarding menstrual cups in a veterinary college in central Kerala, India: a cross-sectional study - Mundodan, Jenyz Mohammedali; Madhusudanan, Chinky; Thanikkaparambil Subran, Anoop; Krishnan, Anupama M.; Ammanath, Aparna; Suresh, Aparna; Nair, Archith; Arjun; Reji, Ashily; Thomas, Ashly Ann; Pattakkal Melakandi, Asif Hassan; Kollaron, Athira; et al. (International Journal Of Community Medicine And Public Health, 2025)
Background: Menstrual cup is a novel, safe, sustainable, cost-effective menstrual product. Despite its advantages, it is not widely accepted in our country, probably due to varied reasons. Objective was to assess the knowledge, attitude and practice of menstrual cups among veterinary college students of central Kerala. Methods: A cross-sectional study was conducted among 177 students at a government veterinary college in Kerala, India. Data was collected using a structured questionnaire to assess knowledge, attitude and practice of menstrual cup. Knowledge score was calculated for all respondents based on eight knowledge-related questions. Practice questions were asked to female students who had used menstrual cups at least once. Results: Thirty of the 177 respondents were male. Majority (84.7%) had adequate knowledge; knowledge was significantly better in females. The most common concern raised by the respondents was the risk of leakage of menstrual blood (30.0%) and breakage of hymen (13.0%). Forty-five respondents had used a menstrual cup at least once, 37 were current users. Insertion, removal and usage were difficult in the initial cycles but later became easier. About one-fifth of the users faced problems like dryness, irritation, allergy or rashes. Conclusions: The study concluded that despite having adequate knowledge regarding menstrual cups, the acceptance and usage is still not achieved.